PP27 What are emergency ambulance services doing to meet the needs of people who call frequently? A national survey of current practice in the united kingdom. Issue 10 (25th September 2020) - Snooks, Helen; Khanom, Ashra; Cole, Robert; Edwards, Adrian; Edwards, Bethan; Evans, Bridie; Foster, Theresa; Fothergill, Rachael; Gripper, Penny; Hampton, Chelsey; John, Ann; Petterson, Robin; et al.
Abstract : Background: Emergency ambulance services are integral to providing a service for those with unplanned urgent and life-threatening health conditions. However, high use of the service by a small minority of patients is a concern. Aims and Objectives: To describe: service-wide and local policies or pathways for people classified as Frequent Caller; call volume; and results of any audit or evaluation. Methods: We conducted a national survey of current practice in ambulance services in relation to the management of people who call the emergency ambulance service frequently using a structured questionnaire, for completion by email and telephone interview. We analysed responses using a descriptive and thematic approach. Results: Twelve of 13 UK ambulance services responded. Most services used nationally agreed definitions for 'Frequent Caller', with 600 – 900 people meeting this classification each month. Service-wide policies were in place, with local variations. Models of care varied from within-service care where calls are flagged in the call centre, contact made with callers and their GP with an aim of discouraging further calls; to case management through cross-service, multi-disciplinary team meetings aiming to resolve callers' needs. No formal audits or evaluations were reported. Conclusions: Ambulance services are under pressure to meet challenging response times for high acuity patients. Tensions are apparent in the provision of care to patients who have complex needs and call frequently. Within service care focused mainly on reducing calls whilst multi-disciplinary case management aimed to resolve clinical and emotional needs of patients. However, there is currently inadequate evidence to inform commissioning, policy or practice development.